Associations between resilience and quality of life in patients experiencing a depressive episode. (October 2020) - Pardeller, Silvia; Kemmler, Georg; Hoertnagl, Christine M.; Hofer, Alex
Highlights: Both QoL and resilience were lower in patients with depressive disorders compared to healthy control subjects. Although there was a significant difference between healthy controls and depressed patients, there was evidence that patients experiencing a depressive episode do not inevitably have low resilience-scores. Within the healthy control group, there were significant correlations between resilience and all WHOQOL-BREF domains. In the patient group resilience correlated exclusively with the WHOQOL-BREF domains global quality of life, psychological health and environment. Abstract: Despite the obvious assumption that resilience affects the course of affective disorders, studies investigating resilience in people experiencing a depressive episode are scarce. The current study explored whether resilience might differently impact quality of life (QoL) in these patients as compared to healthy control subjects. To this end, 60 patients and 75 control subjects were included into a cross-sectional study. In patients, psychopathology was assessed by means of the Montgomery Asberg Depression Rating Scale (MADRS). The Resilience Scale (RS-25) and the WHOQOL-BREF were used in both patients and control subjects to assess resilience and QoL. Depressive patients indicated significantly lower degrees of resilience and QoL compared to healthy subjects. However, there was evidence that patients experiencing a depressive episode do not inevitably have low RS-25 scores. In healthy subjects, a moderate correlation was found between resilience and all WHOQOL-BREF domains, whereas in patients, resilience correlated moderately with global and psychological QoL and with environment. The mediation analysis revealed that the difference in QoL between patients and healthy subjects was partially mediated by resilience. The present study confirms the assumption that resilience is not merely characterized by the absence of psychopathology but is important for the QoL of patients experiencing a depressive episode.